The Effect of Top-of-Rail Products Incorporating Environmentally Acceptable Solid Particles on Friction, Retentivity, Wear and Airborne Particle Emissions of Wheel–Rail Contact - Rahma Boukhris; Ellen Bergseth; Ulf Olofsson; Johan Leckner; Roland Ardai (Machines)
Excessive friction at the wheel–rail contact can limit the lifespan of the wheels and rails. Meanwhile, insufficient friction can lead to increased braking distance, risking safety. Top-of-Rail (TOR) products are recognised for their potential to achieve intermediate friction levels at the wheel–rail contact and mitigate wear damages. However, the impact of these products on the airborne wear particles emitted from wheel–rail contact is not thoroughly evaluated. High particle concentration levels, particularly on underground train platforms, raise respiratory and cardiovascular health concerns. This research employs a pin-on-disc to study the effect of laboratory (environmentally acceptable) and commercial TOR products on friction, retentivity, wear, and airborne particle emissions at the wheel–rail interface. The results indicated that TOR products with higher retentivity offered a wider interval of desired intermediate friction levels. The TOR products significantly reduced particle emissions compared to the dry condition. TOR products can, therefore, be promising in controlling friction and mitigating wear and particle emissions at the wheel–rail interface. However, to achieve the benefits of these products, it is essential to tailor their chemical composition carefully.